Outcome of a large cervicofacial teratoma diagnosed at birth - M. Mayer; A. Delgado; B. Kokose; M. Kopolo; N. Notununu; E. Mntonintshi; N. Dhlomo; K. Namugenyi; S. Mdunge (Elsevier, 2022)
Teratomas are the most common type of germ cell tumours in childhood. Although head and neck teratomas are rare, they carry a high risk of airway obstruction. We report a case of a teenage pregnancy who delivered a male infant at 36 weeks via emergency caesarean section. She attended antenatal care, with no significant prenatal or family history and antenatal ultrasound was not performed. The infant was born with a large cervicofacial teratoma and required resuscitation with bag and mask ventilation at birth with Apgar scores of 6 and 7 at 1 and 5 min respectively. He required intubation to maintain patency of the airway, during which he was noted to have erythematous vocal cords and difficult visualization due to external pressure exerted by the mass on the airway. Complete excision of the mass was performed successfully by a multi-disciplinary team of ear nose and throat and pediatric surgeons after delineating the mass with MRI scan. Infant was discharged home with a tracheostomy tube after a prolonged hospital stay. Intervention soon after birth and a multi-disciplinary approach was critical for survival of this patient.